electrode

The electrode design, featuring a substrate film, inorganic oxide layer, metal underlayer, and conductive carbon layer, addresses the issue of electrolyte durability by preventing electrolyte penetration and improving adhesion, resulting in enhanced performance and longevity.

JP7658973B2Active Publication Date: 2025-04-08NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022538018
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-22
Filing Date
2021-07-20
Publication Date
2025-04-08
Estimated Expiration
2041-07-20

AI Technical Summary

Technical Problem

Conventional electrodes lack excellent electrolyte durability when immersed for long periods, leading to potential damage and reduced performance.

Method used

The electrode structure includes a substrate film, an inorganic oxide layer, a metal underlayer, and a conductive carbon layer, with the inorganic oxide layer acting as a barrier to prevent electrolyte penetration and the carbide layer improving adhesion between the conductive carbon and metal underlayer.

Benefits of technology

This configuration enhances the electrolyte durability of the electrodes, preventing damage from prolonged immersion and maintaining performance over extended periods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658973000002
    Figure 0007658973000002
  • Figure 0007658973000003
    Figure 0007658973000003
  • Figure 0007658973000004
    Figure 0007658973000004
Patent Text Reader

Abstract

[Solution] This electrode is provided with a base material film, an inorganic oxide layer, a metal base layer and a conductive carbon layer sequentially toward one side in the thickness direction.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode. [Background technology]

[0002] 2. Description of the Related Art Conventionally, an electrode has been known that includes a film substrate, a titanium thin film, and a carbon thin film in that order in the thickness direction (see, for example, Patent Document 1 below).

[0003] In the electrode described in Patent Document 1, the titanium thin film improves electrical conductivity while also improving short-term chemical stability. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] WO2016 / 013478 issue Summary of the Invention [Problem to be solved by the invention]

[0005] However, since the electrodes are sometimes immersed in the electrolyte for a long period of time, it is required that the electrodes be capable of suppressing damage caused by the above-mentioned cases, i.e., that the electrodes have excellent durability against the electrolyte.

[0006] However, the electrode described in Patent Document 1 has the drawback of not having the excellent electrolyte durability described above.

[0007] The present invention provides an electrode having excellent electrolyte durability. [Means for solving the problem]

[0008] The present invention (1) includes an electrode comprising, in order toward one side in a thickness direction, a substrate film, an inorganic oxide layer, a metal underlayer, and a conductive carbon layer.

[0009] The present invention (2) includes the electrode according to (1), in which the metal underlayer is capable of forming a carbide together with the carbon of the conductive carbon layer.

[0010] The present invention (3) includes the electrode according to (1) or (2), in which the inorganic oxide layer is a metal oxide layer or a semi-metal oxide layer.

[0011] The present invention (4) includes the electrode according to (3), in which the metal oxide layer and the metal underlayer contain the same metal element.

[0012] The present invention (5) includes the electrode according to (4), in which the metal element is titanium.

[0013] The present invention (6) includes the electrode according to any one of (3) to (5), wherein the semi-metal oxide layer contains silicon dioxide.

[0014] The present invention (7) includes the electrode according to any one of (1) to (6), wherein the metal oxide layer has a thickness of 5 nm or more.

[0015] The present invention (8) includes the electrode according to any one of (1) to (7), which is an electrode for electrochemical measurement. Effect of the Invention

[0016] The electrode of the present invention has excellent durability to an electrolyte. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a cross-sectional view of one embodiment of an electrode of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of an electrode in which a pinhole is formed. [Diagram 3] FIG. 3 is a cross-sectional view of the electrode of Comparative Example 1. [Figure 4] FIG. 4 is a cross-sectional view of the electrode of Comparative Example 2. [Diagram 5]5A and 5B are OM images of the electrode of Example 1. Fig. 5A shows the electrode before immersion in the electrolyte, and Fig. 5B shows the electrode after immersion in the electrolyte. [Figure 6] 6A and 6B are OM images of the electrode of Example 2. Fig. 6A shows the electrode before immersion in the electrolyte, and Fig. 6B shows the electrode after immersion in the electrolyte. [Figure 7] 7A and 7B are OM images of the electrode of Comparative Example 1. Fig. 7A shows the electrode before immersion in the electrolyte, and Fig. 7B shows the electrode after immersion in the electrolyte. [Figure 8] 8A and 8B are OM images of the electrode of Comparative Example 2. Fig. 8A shows the electrode before immersion in the electrolyte, and Fig. 8B shows the electrode after immersion in the electrolyte. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] <One embodiment> One embodiment of the electrode of the present invention will be described with reference to FIGS.

[0019] As shown in Fig. 1, the electrode 1 has a predetermined thickness. The electrode 1 has a film shape (including a sheet shape). The electrode 1 includes a base film 2, an inorganic oxide layer 3, a metal base layer 4, and a conductive carbon layer 5, which are arranged in this order toward one side in the thickness direction. Specifically, the electrode 1 includes only the base film 2, the inorganic oxide layer 3, the metal base layer 4, and the conductive carbon layer 5.

[0020] The base film 2 has a predetermined thickness. Examples of materials for the base film 2 include inorganic materials and organic materials. These can be used alone or in combination. Examples of inorganic materials include silicon and glass. These can be used alone or in combination. Examples of organic materials include resin materials. Examples of resin materials include polyester resins, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, polyarylate resins, and polyphenylene sulfide resins. These can be used alone or in combination.

[0021] The material of the base film 2 is preferably an organic material, more preferably a polyester resin. Specific examples of the polyester resin include polyethylene terephthalate and polyethylene naphthalate. The polyester resin is preferably polyethylene terephthalate.

[0022] There are no particular limitations on the thickness of the base film 2. The thickness of the base film 2 is, for example, 2 μm or more, preferably 20 μm or more, and for example, 1000 μm or less, preferably 500 μm or less.

[0023] The inorganic oxide layer 3 is disposed on one surface in the thickness direction of the base film 2. Specifically, the inorganic oxide layer 3 is in contact with the entire one surface in the thickness direction of the base film 2. The inorganic oxide layer 3 has a predetermined thickness.

[0024] The inorganic oxide layer 3 may be, for example, a metal oxide layer 3A or a semi-metal oxide layer 3B.

[0025] The metal oxide layer 3A is passive. Specifically, the passive layer is made of a metal oxide. Examples of the metal oxide include nickel oxide, cobalt oxide, chromium oxide, titanium oxide, aluminum oxide, tungsten oxide, molybdenum oxide, and composite oxides thereof. These can be used alone or in combination. Preferably, titanium oxide is used from the viewpoint of further improving the durability to the electrolyte.

[0026] The semi-metal oxide layer 3B is made of an oxide of a semi-metal. The semi-metal is not limited. Examples of the semi-metal include silicon, antimony, germanium, and bismuth. A preferable example of the semi-metal is silicon. Specifically, examples of the oxide of a semi-metal include silicon oxide, antimony oxide, germanium oxide, and bismuth oxide. Examples of the oxide of a semi-metal include glass such as borosilicate glass. A preferable example of the oxide of a semi-metal is silicon oxide from the viewpoint of further improving the durability of the electrolyte. Examples of the silicon oxide include silicon dioxide (silica) and silicon monoxide, and a preferable example is silicon dioxide.

[0027] There are no particular limitations on the thickness of the inorganic oxide layer 3. The thickness of the inorganic oxide layer 3 is, for example, 1 nm or more, preferably 5 nm or more, more preferably 5 nm or more, and for example, 50 nm or less, preferably 25 nm or less.

[0028] When the thickness of the inorganic oxide layer 3 is equal to or greater than the above-mentioned lower limit, the inorganic oxide layer 3 has excellent uniformity in the surface direction. The surface direction is a direction perpendicular to the thickness direction. Therefore, the inorganic oxide layer 3 becomes a continuous film, and the effect of improving the electrode durability can be expected.

[0029] On the other hand, if the thickness of the inorganic oxide layer 3 is equal to or less than the above upper limit, the inorganic oxide layer 3 (particularly the metal oxide layer 3A) also has excellent electrical conductivity.

[0030] The metal underlayer 4 is disposed on one surface in the thickness direction of the inorganic oxide layer 3. Specifically, the metal underlayer 4 is in contact with the entire one surface in the thickness direction of the inorganic oxide layer 3. The metal underlayer 4 has a predetermined thickness.

[0031] The material of the metal underlayer 4 is a metal. Such a metal is preferably capable of forming a carbide together with the carbon of the conductive carbon layer 5, which will be described next. Specific examples of such metals include elements of Group 2, Group 4 to Group 14 in the periodic table, and alloys thereof. These can be used alone or in combination.

[0032] Moreover, the metal underlayer 4 and the metal oxide layer 3A contain, for example, the same metal element.

[0033] As a metal for the material of the metal underlayer 4, from the viewpoint of ensuring the chemical stability of the conductive carbon layer 5, preferably, Group 4 elements are used, more preferably, titanium and zirconium are used, and even more preferably, titanium is used.

[0034] It is particularly preferable that the metal oxide layer 3A and the metal underlayer 4 contain titanium as an element. If the metal oxide layer 3A and the metal underlayer 4 contain titanium, this is advantageous because it can improve the adhesion between the metal oxide layer 3A and the metal underlayer 4. When the metal oxide layer 3A contains titanium, the material of the metal oxide layer 3A is titanium oxide. The material of the metal underlayer 4 is titanium as a metal.

[0035] The conductive carbon layer 5 is disposed on one surface in the thickness direction of the metal base layer 4. Specifically, the conductive carbon layer 5 is in contact with the entire one surface in the thickness direction of the metal base layer 4. The conductive carbon layer 5 has a predetermined thickness.

[0036] The material of the conductive carbon layer 5 is carbon, preferably sp 2 Bonds and sp 3 It is a carbon with a bond. 2 Bonds and sp 3Carbon with sp bonds has the graphite type structure and the diamond structure. 3 Number of atoms bonded and sp 2 sp for the sum of the number of atoms bonded 3 The ratio of the number of bonded atoms (sp 3 / sp 3 +sp 2 ) is not particularly limited. 3 / sp 3 +sp 2 ) is, for example, 0.1 or more, preferably 0.2 or more, and for example, 0.9 or less, preferably 0.5 or less. 3 / sp 3 +sp 2 ) is a spectrum obtained by measuring one surface in the thickness direction of the conductive carbon layer 5 by X-ray photoelectron spectroscopy. 2 Bond peak intensity and sp 3 Calculations are based on peak binding intensities.

[0037] The concentration ratio of oxygen to carbon (O / C) on one surface in the thickness direction of the conductive carbon layer 5 is not particularly limited. The concentration ratio (O / C) is, for example, 0.15 or less, preferably 0.10 or less, and is, for example, more than 0.00, 0.01 or more, 0.02 or more, or even 0.03 or more. The concentration ratio is calculated based on the peak area of ​​C1s and the peak area of ​​O1s in a spectrum obtained by measuring one surface in the thickness direction of the conductive carbon layer 5 by X-ray photoelectron spectroscopy.

[0038] The surface resistance value of the conductive carbon layer 5 on one surface in the thickness direction is not particularly limited. The surface resistance of the conductive carbon layer 5 is, for example, 1.0×10 4 Ω / □ or less, preferably 1.0×10 3 The surface resistance is Ω / □ or less. The surface resistance can be measured by the four-terminal method in accordance with JIS K 7194.

[0039] The thickness of the conductive carbon layer 5 is not particularly limited. The thickness of the conductive carbon layer 5 is, for example, 5 nm or more, more preferably 10 nm or more, and is, for example, 200 nm or less, more preferably 100 nm or less. The thickness of the conductive carbon layer 5 is calculated by measuring the X-ray reflectance.

[0040] In addition, a carbide layer (not shown) is preferably formed at the interface between the conductive carbon layer 5 and the metal underlayer 4. The carbide layer is made of carbide, which is a compound of the metal of the metal underlayer 4 and the carbon of the conductive carbon layer 5. The carbide layer improves the adhesion between the conductive carbon layer 5 and the metal underlayer 4. In this case, the electrode 1 includes, in order toward one side in the thickness direction, the base film 2, the inorganic oxide layer 3, the metal underlayer 4, a carbide layer (not shown), and the conductive carbon layer 5.

[0041] Next, a method for manufacturing the electrode 1 will be described. First, a base film 2 is prepared. Next, an inorganic oxide layer 3, a metal underlayer 4, and a conductive carbon layer 5 are formed in this order on one side of the base film 2 in the thickness direction.

[0042] Examples of the method for forming the inorganic oxide layer 3 include a dry method and a wet method. A dry method is preferably used. Examples of the dry method include a PVD method (physical vapor deposition method) and a CVD method (chemical vapor deposition method). A dry method is preferably used. Examples of the PVD method include a sputtering method, a vacuum deposition method, a laser deposition method, and an ion plating method (arc deposition method). A PVD method is preferably used as the sputtering method. The sputtering method is not particularly limited. Examples of the sputtering method include an unbalanced magnetron sputtering method (UBM sputtering method), a high-power pulse sputtering method, an electron cyclotron resonance sputtering method, an RF sputtering method, a DC sputtering method (DC magnetron sputtering method), a DC pulse sputtering method, and an ion beam sputtering method.

[0043] In addition, in the sputtering method, for example, a sputtering gas containing oxygen and an inert gas and a target made of an inorganic substance are used.

[0044] The inert gas may be, for example, argon. The flow rate ratio of oxygen to the total flow rate of the sputtering gas is, for example, 0.01 or more, preferably 0.05, and is, for example, less than 0.5, preferably 0.2 or less.

[0045] Inorganic materials include, for example, metals and metalloids.

[0046] The metal may be a metal element that forms a metal oxide. For example, the metal may be nickel, cobalt, chromium, titanium, aluminum, tungsten, molybdenum, or an alloy thereof. In view of chemical stability, titanium is preferable.

[0047] The metalloids include the above-mentioned metalloids, and preferably silicon.

[0048] The metal underlayer 4 can be formed by the same method as the above-mentioned method for forming the inorganic oxide layer 3. However, when the metal underlayer 4 is formed by a sputtering method, a sputtering gas that does not contain oxygen and contains only an inert gas is used.

[0049] The target material is preferably the same as the target material used in forming the metal oxide layer 3A, and more preferably titanium. Since the same target made of titanium can be used in forming the metal oxide layer 3A and the metal underlayer 4, the design of the manufacturing equipment is simplified.

[0050] The conductive carbon layer 5 can be formed by the same method as the above-mentioned method for forming the inorganic oxide layer 3. However, when the conductive carbon layer 5 is formed by a sputtering method, a sputtering gas containing only an inert gas and no oxygen is used. When the conductive carbon layer 5 is formed by a sputtering method, for example, carbon, preferably sintered carbon, is used as a target material. Thereafter, the conductive carbon layer 5 can be surface-treated as necessary.

[0051] <Effects of one embodiment> This electrode 1 has the base film 2, inorganic oxide layer 3, metal underlayer 4, and conductive carbon layer 5 in that order toward one side in the thickness direction, and therefore has excellent durability to an electrolyte.

[0052] However, as shown in FIG. 2, a pinhole 6 may be inevitably formed in the electrode 1 due to its manufacturing process. The pinhole 6 is a hole penetrating the inorganic oxide layer 3, the metal underlayer 4, and the conductive carbon layer 5 in the thickness direction. For example, when a foreign matter (dust) is inevitably laminated (accumulated) on one surface in the thickness direction of the base film 2 while the base film 2 is being transported, the inorganic oxide layer 3, the metal underlayer 4, and the conductive carbon layer 5 are formed on one side in the thickness direction of the foreign matter. Since the adhesion between the foreign matter and the base film 2 is significantly low, when the foreign matter is detached from one surface in the thickness direction of the base film 2, the corresponding parts of the inorganic oxide layer 3, the metal underlayer 4, and the conductive carbon layer 5 are also detached. This causes the above-mentioned pinhole 6 to be inevitably formed.

[0053] When the electrode 1 is immersed in a corrosive electrolyte, the pinhole 6 is filled with the electrolyte.

[0054] However, as shown in Fig. 3, in an electrode 1 not including an inorganic oxide layer 3 as in Patent Document 1, the electrolyte penetrates into the interface between the metal underlayer 4 and the base film 2 through a pinhole 6 as indicated by a thick arrow. Therefore, the metal underlayer 4 is likely to peel off from one surface in the thickness direction of the base film 2. Therefore, the electrode 1 in Fig. 3 does not have sufficient electrolyte durability.

[0055] In the present application, the electrolyte durability means that the conductive carbon layer 5 is unlikely to be damaged when the electrode 1 is immersed in an electrolyte for a long period of time. Specifically, the electrolyte durability means that the conductive carbon layer 5 is unlikely to be damaged when the electrode 1 is immersed in an electrolyte for, for example, 5 days or more, further 10 days or more, further 15 days or more, or further 20 days or more.

[0056] 4, even in a layer structure in which the order of forming the inorganic oxide layer 3 and the metal underlayer 4 is reversed, the metal underlayer 4 is in contact with one surface in the thickness direction of the base film 2. Therefore, as shown by the arrow in FIG. 4, the electrolyte penetrates into the interface between the metal underlayer 4 and the base film 2 through the pinhole 6.

[0057] However, in this embodiment, even if the pinhole 6 is filled with the electrolyte as shown in Fig. 2, the inorganic oxide layer 3 is provided between the metal underlayer 4 and the base film 2. Therefore, the inorganic oxide layer 3 can prevent the electrolyte from penetrating between the metal underlayer 4 and the base film 2. In other words, the inorganic oxide layer 3 can function as a barrier layer against the electrolyte. Specifically, in the inorganic oxide layer 3, an inner surface 7 facing the pinhole 6 serves as a stopper portion.

[0058] On the other hand, there is a concern that the electrolyte may penetrate into the interface between the conductive carbon layer 5 and the metal underlayer 4, causing the conductive carbon layer 5 to peel off from the metal underlayer 4. However, in this embodiment, a carbide layer is formed at the interface between the conductive carbon layer 5 and the metal underlayer 4. This improves the adhesion between the conductive carbon layer 5 and the metal underlayer 4, making it possible to suppress the above-mentioned penetration. As a result, it is also possible to suppress the conductive carbon layer 5 from peeling off from the metal underlayer 4.

[0059] In addition, if the metal oxide layer 3A and the metal underlayer 4 are made of the same metal element, the adhesion between the metal oxide layer 3A and the metal underlayer 4 can be improved. Furthermore, since targets made of the same metal element can be used for the metal oxide layer 3A and the metal underlayer 4, a common film formation chamber can be used. Therefore, the electrode 1 can be manufactured using compact manufacturing equipment.

[0060] More specifically, if both the metal oxide layer 3A and the metal underlayer 4 contain titanium as an element, the electrode 1 has excellent chemical stability. Furthermore, a common target made of titanium is used in forming the metal oxide layer 3A and the metal underlayer 4, which makes it easier to design the manufacturing equipment.

[0061] Furthermore, if the inorganic oxide layer 3 is a semi-metal oxide layer 3B, the semi-metal oxide layer 3B can effectively prevent the electrolyte from penetrating between the metal underlayer 4 and the base film 2. Therefore, the electrode 1 including the semi-metal oxide layer 3B has excellent electrolyte durability.

[0062] Furthermore, if the thickness of the inorganic oxide layer 3 is 5 nm or more, the inorganic oxide layer 3 has excellent uniformity in the surface direction.

[0063] <Use of electrode 1> The use of the electrode 1 is not particularly limited. For example, the electrode 1 can be used as an electrode for electrochemical measurement. Specifically, the electrode 1 is provided in an electrochemical measurement system including the electrode 1 as a working electrode. EXAMPLES

[0064] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the examples and comparative examples. The specific numerical values ​​of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention".

[0065] Example 1 A base film 2 made of polyethylene terephthalate and having a thickness of 50 μm was prepared.

[0066] Next, a metal oxide layer 3A (inorganic oxide layer 3) made of titanium oxide was formed by magnetron sputtering on one surface in the thickness direction of the base film 2. The conditions for the magnetron sputtering were as follows.

[0067] Target material: Titanium Target power: 100W Sputtering gas: argon and oxygen (flow ratio 9:1) Pressure in sputtering chamber: 0.2 Pa The thickness of the metal oxide layer 3A was 5 nm.

[0068] A metal underlayer 4 made of titanium was formed on one surface in the thickness direction of the metal oxide layer 3A by magnetron sputtering under the following conditions.

[0069] Target material: Titanium Target power: 100W Sputtering gas: Argon Pressure in sputtering chamber: 0.2 Pa The thickness of the metal underlayer 4 was 12 nm.

[0070] A conductive carbon layer 5 was formed by DC pulse sputtering on one surface in the thickness direction of the metal underlayer 4. The conditions for the DC pulse sputtering were as follows. Target material: sintered carbon Argon gas pressure: 0.4 Pa Target power: 3.3W / cm 2 Temperature: 120℃ or less

[0071] The surface resistance of the conductive carbon layer 5 was 130 Ω / □. 3 / sp 3 +sp 2 ) was 0.35. In the conductive carbon layer 5, the concentration ratio of oxygen to carbon (O / C) was 0.06. The thickness of the conductive carbon layer 5 was 30 nm.

[0072] In this way, an electrode 1 was produced which was provided with the base film 2, the metal oxide layer 3A, the metal underlayer 4, and the conductive carbon layer 5 in this order towards one side in the thickness direction.

[0073] Example 2 The same treatment as in Example 1 was carried out except that the thickness of the metal oxide layer 3A was changed to 2 nm.

[0074] Example 3 Except for forming a semi-metal oxide layer 3B instead of the metal oxide layer 3A, the same treatment as in Example 1 was carried out. That is, a semi-metal oxide layer 3B (inorganic oxide layer 3) made of silicon dioxide was formed on one surface in the thickness direction of the base film 2 by magnetron sputtering. The conditions for the magnetron sputtering method are as follows.

[0075] Target material: Silicon Target power: 700W Sputtering gas: argon and oxygen (flow ratio 7:3) Sputtering pressure: 0.3Pa The thickness of the semi-metal oxide layer 3B was 10 nm.

[0076] Example 4 The same process as in Example 1 was carried out, except that the thickness of the semi-metal oxide layer 3B was changed to 5 nm.

[0077] Comparative Example 1 Except for not forming the metal oxide layer 3A, the electrode was treated in the same manner as in Example 1. That is, as shown in Fig. 3, this electrode 1 was provided with a base film 2, a metal underlayer 4, and a conductive carbon layer 5 in this order toward one side in the thickness direction.

[0078] Comparative Example 2 Except for switching the order of forming the metal oxide layer 3A and the metal underlayer 4, the electrode 1 was treated in the same manner as in Example 1. That is, as shown in Fig. 4, the electrode 1 was provided with a base film 2, a metal underlayer 4, a metal oxide layer 3A, and a conductive carbon layer 5 in this order toward one side in the thickness direction.

[0079] <Evaluation> The following items were evaluated for the electrodes 1 of each of the examples and comparative examples. The results are shown in Table 1.

[0080] <Durability of electrolyte> An insulating tape 9 was attached to one surface in the thickness direction of the conductive carbon layer 5 as shown by the imaginary lines in each of Figures 1, 3 and 4. The insulating tape 9 had an opening 8 with a diameter of 2 mm.

[0081] The electrode 1 and the insulating tape 9 were immersed in a 0.1 M nitric acid solution for 56 days.

[0082] Optical microscope images (hereinafter referred to as OM images) of the electrode 1 and insulating tape 9 before and after immersion are shown in Figs. 5A to 8B. Figs. 5 to 8 correspond to Example 1 to Comparative Example 2, respectively. Fig. 5A shows the electrode 1 before immersion in Example 1. Fig. 5B shows the electrode 1 after immersion in Example 1. Figs. 6A to 8B are similar to Figs. 5A to 5B described above.

[0083] From the OM images after immersion, the electrolyte durability was evaluated based on the following criteria.

[0084] ◯: As can be seen from FIG. 5B, almost no damage caused by pinhole formation was observed. △: As can be seen from FIG. 6B, a few damaged areas due to pinhole formation were observed. ×: As can be seen from FIG. 7B and FIG. 8B, damage sites due to pinhole formation were observed to a considerable extent.

[0085] <Electrode characteristics> The potential window of electrode 1 of each example to each comparative example was measured using a potentiostat, thereby evaluating the electrode characteristics of electrode 1. The potential window means a voltage range in which no current flows even when a voltage is applied, and the wider the range, the better the electrode characteristics of electrode 1.

[0086] An electrochemical measurement system was constructed that included the electrode 1 as a working electrode. This electrochemical measurement system also included an Ag / AgCl electrode as a reference electrode and a Pt electrode as a counter electrode.

[0087] Then, the electrode 1 was immersed in a 0.1 M sulfuric acid solution. Then, a potential was swept to the electrode 1, and the potential was 500 μA / cm 2 The width of the potential when the potential reaches the threshold value was defined as the potential window.

[0088] As can be seen from Table 1, in all of Example 1 to Comparative Example 2, the potential window is 3.7 or more, and therefore the electrode characteristics of the electrode 1 before immersion are good.

[0089] [Table 1]

[0090] The above invention is provided as an exemplary embodiment of the present invention, but this is merely an example and should not be interpreted as being limited. Modifications of the present invention that are obvious to those skilled in the art are included in the scope of the following claims. [Industrial Applicability]

[0091] The electrodes are used, for example, in electrochemical measurements. [Explanation of symbols]

[0092] 1 electrode 2. Base film 3. Inorganic oxide layer 3A metal oxide layer 3B Metalloid oxide layer 4 Metal base layer 5 Conductive carbon layer

Claims

1. A substrate film, an inorganic oxide layer, a metal underlayer, and a conductive carbon layer are provided in this order toward one side in a thickness direction, An electrode, wherein in the conductive carbon layer, a ratio of the number of sp 3 bonded atoms to the sum of the number of sp 3 bonded atoms and the number of sp 2 bonded atoms (sp 3 / sp 3 +sp 2 ) is 0.1 or more and 0.9 or less.

2. The electrode according to claim 1 , wherein the metal underlayer is capable of forming a carbide with carbon of the conductive carbon layer.

3. 3. The electrode according to claim 1, wherein the inorganic oxide layer is a metal oxide layer or a semi-metal oxide layer.

4. The electrode according to claim 3 , wherein the metal oxide layer and the metal underlayer contain the same metal element.

5. 5. The electrode according to claim 4, characterized in that the metallic element is titanium.

6. 6. The electrode according to claim 3, wherein the semi-metal oxide layer comprises silicon dioxide.

7. 6. The electrode according to claim 1, wherein the inorganic oxide layer has a thickness of 5 nm or more.

8. The electrode according to claim 6, wherein the inorganic oxide layer has a thickness of 5 nm or more.

9. The electrode according to any one of claims 1 to 5, which is an electrode for electrochemical measurements.

10. 7. The electrode according to claim 6, which is an electrode for electrochemical measurements.

11. 8. The electrode according to claim 7, which is an electrode for electrochemical measurements.

12. 9. The electrode according to claim 8, which is an electrode for electrochemical measurements.

Citation Information

Patent Citations

  • Hollow structure element

    JP2010204029A

  • Density measuring sensor and manufacturing method thereof

    JP2013185991A

  • Electrode film and electrochemical measurement system

    JP2019105637A

  • Modified graphitic electrodes for electrochemical energy storage enhancement

    US20140322608A1

  • Thin film-laminated film

    WO2016013478A1